Measurement Of Radiation Dose During ExtraCorpearal ShockWave Lithotripsy Procedure - Bushara, Nada AA; Sulieman, Abdelmoneim; Halato, Mohamed A; Suliman, Ibrahim I. (Asian Journal of Medical Radiological Research, 2012)
Extracorporeal shock wave lithotripsy (ESWL) is considered the gold standard in vivo treatment process for renal, uretric and kidney stones. This procedure is usually followed up by using x-ray fluoroscopy device. Therefore, optimization the absorbed dose of patients is crucial ; the aim of this study is to measure the entrance surface dose, organ dose and the probability of carcinogenesis regarding to x-ray fluoroscopy irradiating during ESWL. The study was performed in Al-Naileen diagnostic center (group A, 33 patient) and in Al-Khartoum advance diagnostic center (group B, 18 patients), the entrance surface doses (ESD) measurements were performed using thermoluminescence dosimeter (TLDs) GR200A LiF. The mean entrance surface dose and mean effective dose were (0.34 mGy & 0.014 mGy) and (0.22mGy & 0.01 mGy) for groupA and B respectively. The estimated organ dose were (0.16 mGy), (0.02) and (0.01) for kidneys, intestines and ovaries in that order. Group A was irradiated to higher dose than group B due to the X ray machine characteristics and techniques. The results show that the probability of carcinogenesis is a tiny value (1 for million patient. In addition the study insures that there is a correlation between the weights, irradiating factors and absorbed doses; as a result guiding charts, training courses for technician and a strong quality assurance program were recommended to optimize the ESD for patients.